DIGITAL PAYMENT TRANSFORMATION: THE ROLE OF THE TECHNOLOGY ACCEPTANCE MODEL TO REPURCHASE INTENTION - Sutrisno, Timotius F.C.W. (International Business Management - Universitas Ciputra, 2023)
Changes in the interaction between humans and technology have begun. The existence of technological developments cannot be separated from changes in the pattern of public transactions, which were initially traditional systems into digital systems. This research looks at the factors influencing user repurchase intentions, such as TAM factors and technology attributes, which are very important. This is quantitative research using SEM-PLS. The results showed that the variable Trust mediates the relationship between Security and Privacy Concerns on Repurchase Intention. E-Satisfaction mediates the relationship between Ease of Use, Security, and Privacy Concerns on Repurchase Intention. This research is a form of development of the TAM, which was carried out in Surabaya, so it does not reach all parts of Indonesia. This is because digital payments have not been used evenly, so the results obtained have not projected the acceptance behavior of the Indonesian people as a whole.